Discovery of Early Mesozoic Magmatism in the Northern Muglad Basin (Sudan): Assessment of Its Impacts on Basement Reservoir - Zhao, Jian; Dou, Lirong (Frontiers in Earth Science, 2022)
The crystalline basement in the Central African Rift System (CARS) has been confirmed as a good unconventional reservoir in the surrounding basins of the Muglad area, Sudan. This study has recognized at least five Early Mesozoic intrusions for the first time at the northern margin of the Muglad Basin. Field and petrographic investigations show that they are mainly granite, syenite, diorite, and monzonite, with dominant alkali feldspar, plagioclase, quartz, and minor hornblende, biotite, and magnetite. Zircon internal structures, Th/U ratios, and rare earth element (REE) patterns indicate their magmatic origin. A total of 210 zircons from five samples were analyzed using LA-ICP-MS and they yielded U-Pb ages from 195.0 ± 6 to 225.0 ± 3 Ma, belonging to the Late Triassic-Early Jurassic. These results suggest that the Muglad Basin basement is not universally Precambrian as previously considered. The older basement was intruded and modified by Early Mesozoic magmas as evidenced by field contacts and our dating results. These magmatic events produced diverse Mesozoic igneous rocks prior to the formation of the Muglad Basin (Early Cretaceous), becoming new members of the crystalline basement. This composite basement then experienced prolonged weathering and fracturing for 65–95 Ma, resulting in porous and permeable weathered layers or fractured zones, making the basement a good unconventional reservoir for oil and gas.